Locomotion of Multi Arm Robot for In-Orbit Operations (MARIO) in lab environment - Elavazhagan, Praveen; Leslie, Cameron; Upadhyay, Saurabh; Tang, Gilbert; Felicetti, Leonard (Springer, 2026)
This paper presents the control architecture and experimental validation of MARIO, a multi-arm robotic platform developed by Cranfield University for In-Orbit Servicing and Manufacturing (IOSM) task demonstration in a laboratory environment. MARIO comprises three ROS-enabled, 6-degree-of-freedom robotic arms with a 5 kg payload capacity, mounted on a pneumatic air-bearing platform that enables near-frictionless planar movement over an epoxy floor. Each arm is equipped with onboard cameras and end-effectors to perform locomotion, assembly, and manipulation tasks with high precision. The developed ROS2-based control framework integrates a multi-layered architecture, combining a collision-free trajectory planner, synchronized multi-arm coordination, and hardware-level execution for smooth and accurate motion. The platform is experimentally validated in the laboratory through arm-based locomotion and coordinated base-arm movements using standard interfaces. The resulting control architecture can be used as the foundation for developing a common framework of the multi-arm robot in orbital application.
Keywords: 46 Information and Computing Sciences; Bioengineering; Artificial Intelligence & Image Processing; 46 Information and computing sciences; Space Robotics; Control framework; Multi-Arm Robot; Assembly; Locomotion; ROS2; IOSM